Sustainable Production of Nannochloris atomus Biomass Towards Biodiesel Production - Touria Bounnit (16936899) (2020)
Nannochloris atomus (QUCCCM31) is a local marine microalga showing potential to serve as renewable feedstock for biodiesel production. The investigation of the impact of temperature variation and nitrogen concentrations on the biomass and lipid productivities evidenced that biomass productivity increased with the temperature to reach an optimum of 195 mgL−1 d−1 at 30 °C. Similarly, the lipid content was strongly influenced by the elevation of temperature; indeed, it increased up to ~3 folds when the temperature increased from 20 to 40 °C. When both stresses were combined, triacylglycerols and lipid productivity reached a maximum of 45% and 88 mgL−1 d−1, respectively at 40 °C. Cultures under high temperatures along with Nitrogen-Depleted (ND) favored the synthesis of Fatty Acids Methyl Ester (FAMEs) suitable for high quality biodiesel production, whereas cultures conducted at low temperature coupled with Nitrogen-Limited (NL) led to a production of polyunsaturated fatty acids (PUFAs). Our results support the feasibility of cultivating the thermotolerant isolate QUCCCM31 year-round to meet the sustainability challenges of algal biomass production by growing under temperature and nitrogen variations. The presence of omega 3 and 9 fatty acids as valuable co-products will help in reducing the total process cost via biorefinery. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su12052008